The Influence Of Health Education On The Behavior Of Handling Musculoskeletal Injury - Linda, Linda (Jurnal EduHealth, 2022)
Background: Musculoskeletal injuries are the most global health problem due to their high prevalence, especially among workers. Low behavior in handling musculoskeletal injuries can cause health problems, namely musculoskeletal injuries. Objective: This study aimed to determine the effect of health education on behavioral changes in the management of musculoskeletal injuries in injured patients in the Basirih South sub-district, South Banjarmasin. Method: This type of research used a quantitative pre-experimental design with one group pretest-posttest design. This research was conducted in Basirih South Village, South Banjarmasin, on November 10, 2021, with a research sample of 36 respondents using a total sampling technique. The instrument was a questionnaire tested for validity and then distributed door-to-door. The data was processed using the Non-Parametric Wilcoxon signed ranks test. Results: Based on the behavior of handling musculoskeletal injuries in injured patients during the pretest, the results showed that the majority (66.7%) had lousy behavior in 24 patients. And after health education was carried out during the post-test, there was an increase in the number of sufferers (88.9%) having good behaviour of 32 injured patients. Using the Non-Parametric Wilcoxon Signed Ranks Test hypothesis, the analysis results obtained a p-value = 0.000. This means P value <0.05 (Ho is rejected, Ha is accepted) means "The Influence of Health Education on the Behavior of Handling Musculoskeletal Injury in Injured Patients in Basirih South Village, South Banjarmasin." Conclusion: Health education can influence behavior in handling musculoskeletal injuries, which can change behavior and increase understanding of managing musculoskeletal injuries in injured patients.